Catholicism and Democracy: An Essay in the History of Political Theory - Kennedy, Robert Emmet (A journal of church and state, 2014)
Catholicism and Democracy: An Essay in the History of Political Theory is not a history of church and state but an intellectual history of Catholicism and the state. The book is based on secular political theory rather than historical narrative the sociology of religious practice. Within these confines, Perreau-Saussine's work is an immensely valuable, concise overview that confronts perennial questions with new, often unfamiliar, evidence. The work is all the more remarkable because it is the last of a scholar who died suddenly in 2010 at the age of thirty-seven. The author defines French Gallicanism as an attempt to prevent all ecclesiastical interference in the state.